DEEP-South: Preliminary Photometric Results from the KMTNet-CTIO. Issue Volume 10:Issue S318(2015) (1st March 2016) - Kim, Myung-Jin; Moon, Hong-Kyu; Choi, Young-Jun; Yim, Hong-Suh; Bae, Young-Ho; Roh, Dong-Goo; Park, Jin Tae; Moon, Bora; ,
Abstract: Korea Astronomy and Space Science Institute (KASI) successfully completed the development of Korea Microlensing Telescope Network (KMTNet, Park et al .2012 ) in mid-2015, following which it conducted test runs for several months. 'DEep Ecliptic Patrol of the Southern sky' (DEEP-South, Moon et al .2015 ), which will be used for asteroid and comet studies, will not only characterize targeted asteroids, carrying out blind surveys toward the sweet spots, but will also mine the data of such bodies using the KMTNet archive. We report preliminary lightcurves of four Potentially Hazardous Asteroids (PHAs) from test runs at KMTNet-CTIO in the February - May 2015 period.